Large-Scale Preparation of Highly Stable Recombinant Human Acidic Fibroblast Growth Factor in Escherichia coli BL21(DE3) plysS Strain - Yu, Bingjie; Sun, Wenzhe; Huang, Zhen; Sun, Gang; Li, Le; Gu, Jiawei; Zheng, Mengying; Li, Xiaokun; Chun, ChangJu; Hui, Qi; Wang, Xiaojie (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, the optimum human aFGF gene encoding haFGF135 was cloned in pET3c and transferred to Escherichia coli BL21(DE3) plysS. To enhance the yield of fermentation and the expression level of the target protein, the fermentation parameters, including temperature, pH, dissolved oxygen, glucose concentration, ammonium chloride concentration, induction time, and inducer (IPTG) concentration, were optimized. The optimized fermentation parameters were used in large-scale fermentation (30 L). Ion-exchange and heparin-affinity column chromatography techniques were used for separation and purification of rhaFGF135 protein. HPLC, isoelectric focusing electrophoresis, and mass spectrometry were used to detect the purity, isoelectric point, and molecular weight and peptide map of rhaFGF135 protein, respectively. Mitogenic activity of rhaFGF135 protein was detected in NIH-3T3 cells and a full-thickness injury wound diabetic rat model. The production and expression level of rhaFGF135 in the 30-L scale fermentation reached 80.4 ± 2.7 g/L culture and 37.8% ± 1.8%, respectively. The RP-HPLC and SDS-PAGE purity of the final rhaFGF135 product almost reached 100%, and the final pure protein yield was 158.6 ± 6.8 mg/L culture. Finally, the cell and animal experiments showed that rhaFGF135 retained a potent mitogenic activity. The large-scale process of rhaFGF135 production reported herein is relatively stable and time-saving, and thus, it can be used as an efficient and economic strategy for the synthesis of rhaFGF135 at the industrial level.